Catalytic deoxygenation of C18 fatty acid over supported metal Ni catalysts promoted by the basic sites of ZnAl2O4 spinel phase. Issue 1 (6th December 2018) - Li, Guangci; Chen, Lei; Fan, Ruikun; Liu, Di; Chen, Song; Li, Xuebing; Chung, Keng H.
Abstract : The supports with various amounts of Zn–Al spinel were synthesized to test catalytic deoxygenation activity of fatty acids, which show that spinel phase increased the basic strength of the catalyst, resulting in a high selectivity to hydrocarbons. Abstract : Highly active Zn–Al composite oxides were synthesized via a hydrothermal process followed by thermal treatment and were used as supports to prepare Ni-based hydrogenation catalysts for catalytic deoxygenation of oleic acid, stearic acid, and 1-octadecanol. The results showed that increasing the temperature of hydrothermal synthesis changed the morphology of the Zn–Al composite oxides from sheet-like structures to spheroidal structures. High hydrothermal synthesis temperatures enhanced the interaction between Zn and Al atoms, resulting in more ZnAl2 O4 spinel phase. This phase not only improved the chemical stability of the support but also supplied strong basic sites which efficiently inhibited the formation of by-products and increased the yield of heptadecane in the catalytic deoxygenation of oleic acid. Stearic acid and 1-octadecanol could be readily transformed to alkanes in the presence of metallic Ni and ZnAl2 O4 phase. Decarbonylation of the octadecanal intermediate and dehydrogenation of 1-octadecanol were key reaction pathways to produce heptadecane, in which decarbonylation was catalyzed by metallic Ni, while the dehydrogenation was attributed to synergistic catalysis between metallic Ni and the strong basic sites of the support. Individual metallic Ni only catalyzed the cleavage of C–H bonds but did not affect the O–H bond of 1-octadecanol.